The Effect of the Implementation of the Postpartum Care Laboratory Skill Integrated Learning Model on Improving the Competence - Abdurrahman Abdurrahman; Cut Mutiah; Halimatussakdiah Halimatussakdiah (Postgraduate, University of Mataram, 2023)
The conventional laboratory learning model has proven to be inadequate in improving competencies. Therefore, there is a need to develop a learning model that integrates the knowledge gained with the skills and attitudes required when providing care, namely an integrated laboratory skills learning model. The purpose of this study was to analyze the effect of the implementation of an integrated postpartum care laboratory skill learning model on improving the competencies of Diploma-3 midwifery students. This study adopted a quasi-experimental pretest-posttest nonequivalent control group design with 79 students divided into two groups: the intervention group consisting of 39 students from STIKes Indramayu and the control group consisting of 40 students from Poltekkes BPH Cirebon. The intervention group was given the integrated learning model, while the control group was given the conventional learning model. Data analysis was conducted using t-tests, Mann-Whitney tests, and chi-square tests with a significance level of p<0.05. The results showed that the pretest competencies of the intervention group were 33 (84.6%) who were not competent, while in the control group, 35 (87.5%) were not competent. There was an increase in competencies in the intervention group by 49% (0-887) and in the control group by 19.4% (0-50.9). Further analysis indicated a significant difference in competency improvement between the group given the integrated laboratory skills learning model and the group given the conventional laboratory skills learning model (p<0.05). The conventional laboratory skills learning model was a risk factor causing students to be incompetent with a relative risk of 1.64 (95% CI 1.15-2.35) and NNT 3.2. The Integrated model of laboratory skills has a positive impact on students’ skill elevation.